Survival rate of ceramic inlay and onlay restorations in posterior teeth with one-surface or multi-surface after a 10-year follow-up: A systematic review and meta-analysis - Yun, Zou; Jing, Bai; Jing, Zhou Xiang (Vojnosanitetski pregled, 2021)
Background/Aim. A large number of studies have been conducted on the survival rate of ceramic single tooth restorations, but few studies have discussed the influence of the number of restoration surfaces on their survival rate. This study aimed to evaluate the survival rate of ceramic inlay and onlay restorations in posterior teeth with one-surface or multi-surface after a 10-year follow-up. Methods. PubMed, Web of Science, Cochrane Library, Embase, and Wanfang databases were searched for articles published by July 31, 2016. Randomized controlled trials and non-randomized trials were collected and patients with posterior teeth defect were included. Publication bias and sensitivity analysis were also assessed. Results. Five studies comprising 6,720 cases were included in this meta-analysis. The results indicated that the survival rate of ceramic inlay and onlay restorations with two-surface was significantly higher than that of one-surface restorations (within 10 years) [hazard ratio (HR) = 2.11; 95% confidence interval (CI) = 1.33–3.36, p = 0.002], and the survival rate of three-surface restorations was higher than that of two-surface ones (HR = 2.50; 95% CI = 1.36–4.59, p = 0.003). Conclusion. The current meta-analysis shows that the increase in the ceramic inlay and onlay restoration surfaces increases their survival rate within a 10-year period.
Keywords: denture, partial, fixed; meta- analysis as topic; survival rate